2000
DOI: 10.1161/01.res.86.10.1062
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Renin-Angiotensin System on the Current I to in Epicardial and Endocardial Ventricular Myocytes From the Canine Heart

Abstract: The Ca(2+)-independent portion of transient outward K(+) current (I(to)) exhibits a transmural gradient in ventricle. To investigate control mechanisms for this gradient, we studied canine epicardial and endocardial ventricular myocytes with use of the whole-cell patch-clamp technique. I(to) was larger in amplitude, had a more negative voltage threshold for activation, and had a more negative midpoint of inactivation in epicardium. Recovery from inactivation was >10-fold slower in endocardium. Incubation of ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
113
1
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(127 citation statements)
references
References 28 publications
10
113
1
3
Order By: Relevance
“…The down-regulation of I to might be, at least in part, responsible for the arrhythmogenic potential of angiotensin II. Experiments with isolated cardiomyocytes demonstrated that angiotensin II inhibits I to in rat and canine myocytes (15,16). As with other G q -coupled receptors (e.g.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…The down-regulation of I to might be, at least in part, responsible for the arrhythmogenic potential of angiotensin II. Experiments with isolated cardiomyocytes demonstrated that angiotensin II inhibits I to in rat and canine myocytes (15,16). As with other G q -coupled receptors (e.g.…”
Section: Discussionmentioning
confidence: 85%
“…One important difference between protein kinase C-dependent inhibition of I to in Xenopus oocytes and the angiotensin II-dependent inhibition of I to in canine cardiomyocytes (16) or HEK 293 cells is the change in the activation voltage threshold of Kv4. 3.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1B); additionally, I to is sensitive to 4-AP. 15 Pursuing the hypothesis that stretch-activated angiotensin II release occurs in cardiac memory, Yu and colleagues 16 demonstrated that application of angiotensin II to epicardial myocytes resulted in a marked reduction in I to density, a shift in current activation to more depolarized potentials, and a slowing of recovery from inactivation, all of which resulted in an electrical phenotype (in epicardial cells) more similar to endocardial cells. No changes in the expression levels of the transcripts encoding the K V 4.3 (KCND3) or K V 1.4 (KCNA4) subunits which encode I to channels (Fig.…”
Section: Ion Channel Remodeling In Short-term Cardiac Memorymentioning
confidence: 99%